KONDISI SOSIAL EKONOMI DAN TINGKAT KESEJAHTERAAN KELUARGA: KASUS DI WILAYAH PESISIR JAWA BARAT - Istiqlaliyah Muflikhati; Hartoyo Hartoyo; Ujang Sumarwan; Achmad Fahrudin; Herien Puspitawati (Jurnal Ilmu Keluarga dan Konsumen, 2010)
Family welfare is influenced by socio-economic factors like sociodemographic of family, family income, and position in society. This research compared characteristics and family welfare between fishermen families and non-fishermen families in coastal West Java. This research also analyzed the effect of social economy of family toward family welfare. This research involved 280 families as samples, consist of 157 fishermen families and 123 non-fishermen families. The research conducted in eight villages of four coastal subdistricts in West Java Province. The were no significant differences on family types, father’s and mother’s age, value of total assets, and per capita expenditure between fishermen and non-fishermen families. Father’s and mother’s education of fishermen families were significantly lower than father’s and mother’s education of non-fishermen families. On the contrary, family size and per capita income in fishermen families significantly were higher than nonfishermen families. Fishermen families had higher level welfare than non-fishermen families used World Bank and BPS’s poverty line indicators, but by BKKBN, poverty household criteria, and socio-metric indicators fishermen families had lower than nonfishermen families.